Trait to gene analysis reveals that allelic variation in three genes determines seed vigour. Issue 4 (19th July 2016) - Morris, Karl; Barker, Guy C.; Walley, Peter G.; Lynn, James R.; Finch‐Savage, William E.
Summary: Predictable seedling establishment is essential for resource‐efficient and cost‐effective crop production; it is widely accepted as a critically important trait determining yield and profitability. Seed vigour is essential to this, but its genetic basis is not understood. We used natural variation and fine mapping in the crop Brassica oleracea to show that allelic variation at three loci influence the key vigour trait of rapid germination. Functional analysis in both B. oleracea and the model Arabidopsis identified and demonstrated activity of genes at these loci. Two candidate genes were identified at the principal Speed of Germination QTL ( SOG1 ) in B. oleracea . One gene BoLCVIG2 is a homologue of the alternative‐splicing regulator ( AtPTB1 ). The other gene BoLCVIG1 was unknown, but different alleles had different splice forms that were coincident with altered abscisic acid (ABA) sensitivity. We identified a further QTL, Reduced ABscisic Acid 1 ( RABA1 ) that influenced ABA content and provide evidence that this results from the activity of a homologue of the ABA catabolic gene AtCYP707A2 at this locus. Lines containing beneficial alleles of these three genes had greater seed vigour. We propose a mechanism in which both seed ABA content and sensitivity to it determines speed of germination.